Detection and quantification of alkali-silica-reaction (ASR) gel in cement-based mortars using microwave spectral and temporal transmission properties. (15th June 2023) - Hasar, Ugur Cem; Ozturk, Hamdullah; Korkmaz, Huseyin; Tasdemir, Ahmet; Bute, Musa; Nis, Anil; Karaaslan, Muharrem; Cevik, Abdulkadir; Ozkaya, Mehmet Akif
Abstract: Microwave transmission measurements in time-domain, as a new measurement tool, were carried out to detect and quantify alkali-silica-reaction (ASR) within mortar specimens. To examine the potential of time-domain transmission measurements for ASR detection and its any possible quantification, transmission measurements in frequency-domain and time-domain of two different sets (reactive and non-reactive) of mortar specimens were performed approximately every 2 or 3 days over 29 days after demolding the specimens, by a rectangular waveguide operated at 2.60–3.95 GHz. Thickness expansion measurements of reactive and non-reactive sets were also performed. Additionally, SEM micrographs and energy-dispersive X-ray spectroscopy tests of specimens were implemented to support microwave and expansion measurements. After performing some analysis for the correlation between microwave and expansion measurements, it is observed for the first time in the literature that transmission measurements via expansion tests could be effectively applied for quantification of ASR level within cement-based materials. Highlights: Time-domain microwave measurements are utilized to detect and quantify the alkali-silica-reaction. Amplitude decay and propagation delay of the transmission measurements are performed. Reactive and non-reactive sets of mortar specimens are prepared. SEM, EDS, thickness expansion tests of specimens are also examined.